Alien Hand, Restless Brain: Salience Network and Interhemispheric Connectivity Disruption Parallel Emergence and Extinction of Diagonistic Dyspraxia - Ridley, Ben; Beltramone, Marion; Wirsich, Jonathan; Le Troter, Arnaud; Tramoni, Eve; Aubert, Sandrine; Achard, Sophie; Ranjeva, Jean-Philippe; Guye, Maxime; Felician, Olivier (Frontiers in Human Neuroscience, 2016)
Diagonistic dyspraxia (DD) is by far the most spectacular manifestation reported by sufferers of acute CC injury (so-called ‘split-brain’). In this form of alien hand syndrome, one hand acts at cross purposes with the other ‘against the patient’s will’. Although recent models view DD as a disorder of motor control, there is still little information regarding its neural underpinnings, due to widespread connectivity changes produced by CC insult, and the obstacle that non-volitional movements represent for task-based functional neuroimaging studies. Here, we studied patient AM, the first report of diagonistic dyspraxia in patient with complete developmental CC agenesis. This unique case also offers the opportunity to study the resting-state connectomics of diagonistic dyspraxia in the absence of diffuse changes subsequent to CC injury or surgery. AM developed diagonistic dyspraxia following status epilepticus which resolved over a 2 year period. Whole brain functional connectivity (FC) was compared (Crawford-Howell) to 16 controls during the period of acute DD symptoms (Time 1) and after remission (Time 2). Whole brain graph theoretical models were also constructed and topological efficiency examined. At Time 1, disrupted FC was observed in inter-hemispheric and intra-hemispheric right edges, involving frontal superior and midline structures. Graph analysis indicated disruption of the efficiency of salience and right frontoparietal networks. At Time 2, after remission of diagnostic dyspraxia symptoms, FC and salience network changes had resolved. In sum, longitudinal analysis of connectivity in AM indicates that DD behaviors could result from disruption of systems that support the experience and control of volitional movements and the ability to generate appropriate behavioral responses to salient stimuli. This also raises the possibility that changes to large-scale functional architecture revealed by resting-state fMRI may provide relevant information on the evolution of behavioral syndromes in addition to that provided by structural and task-based functional imaging.